A Review on: Impacts of Climate Change on Himalayan Glaciers and its Ecosystems ... - Tinkal Patel; Ruchita Mainani; Pragati Nayak; Hitesh Solanki (Zenodo, 2023)
The Himalayan Range is one of the world's most important and highest mountain ranges. It is found over various countries. The Himalayas were formed approximately 50 million years ago when the Eurasian plate collided with the Indian plate. This area is home to about 50 million people. The Himalayan areas are abundant in biodiversity and water resources. This research examines the changing climatic scenario of glaciers and their ecosystems as a result of atmospheric and anthropogenic activity. Species are becoming more vulnerable to extinction as a result of climate change. Climate change has previously had a devastating influence on Himalayan biodiversity ranges. Climate change will also have an impact on the lives and food security of the region's residents, who rely on the mountains' natural resources. According to the Intergovernmental Panel on Climate Change's fourth assessment report (IPCC, 2007), "the majority of the observed increase in globally averaged temperatures since the mid-20th century is very ... : {"references": ["Adler, C., Huggel, C., Orlove, B., & Nolin, A. (2019). Climate change in the mountain cryosphere: impacts and responses. Regional Environmental Change, 19, 1225-1228.", "Ahmed, R., Wani, G. F., Ahmad, S. T., Sahana, M., Singh, H., & Ahmed, P. (2021). A review of glacial lake expansion and associated glacial lake outburst floods in the Himalayan region. Earth Systems and Environment, 5(3), 695-708", "Allen, S. K., Rastner, P., Arora, M., Huggel, C., & Stoffel, M. (2016). Lake outburst and debris flow disaster at Kedarnath, June 2013: hydrometeorological triggering and topographic predisposition. Landslides, 13, 1479-1491.", "Azam, M. F., Wagnon, P., Berthier, E., Vincent, C., Fujita, K., & Kargel, J. S. (2018). Review of the status and mass changes of Himalayan-Karakoram glaciers. Journal of Glaciology, 64(243), 61-74.", "Chakraborty, A., Saha, S., Sachdeva, K., & Joshi, P. K. (2018). Vulnerability of forests in the Himalayan region to climate change impacts and ...